Propagation and spread of pathogenic protein assemblies in neurodegenerative diseases - Jucker, Mathias (Nat Neurosci, 2018)
Many neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis are characterized by the progressive appearance of abnormal proteinaceous assemblies in the nervous system. Studies in experimental systems indicate that the assemblies originate from the prion-like seeded aggregation of specific misfolded proteins that proliferate and amass to form the intracellular and/or extracellular lesions that are typical of each disorder. The host in which the proteopathic seeds arise provides the biochemical and physiological environment that either supports or restricts their emergence, proliferation, self-assembly and spread. Multiple mechanisms influence the spatiotemporal spread of seeds and the nature of the resulting lesions, one of which is the cellular uptake, release, and transport of seeds along neural pathways and networks. The characteristics of cells and regions in the affected network govern their vulnerability and thereby influence the neuropathological and clinical attributes of the disease. The propagation of pathogenic protein assemblies within the nervous system thus is determined by the interaction of the proteopathic agent and the host milieu.